Advancements in the development of various types of dye-sensitized solar cells: A comparative review - Bai, Sandhia; Amirruddin, Abdul Kadir; Pandey, A. K.; Samykano, M.; Muhammad Shakeel, Ahmad; Sharma, Kamal; Tyagi, V. V. (Tech Science Press, 2021)
The global increase in energy demand has resulted in the depletion of non-renewable resources and caused environmental degradation. Consequently, emerging renewable technologies are a potential solution to fulfil energy demand and mitigate the effect of global warming. Low-cost solar energy harvesting technologies are most feasible technologies. Various solar cells technologies have been developed with improved overall performance and conversion efficiency. However, due to low cost and a wide range of applications, dye-sensitized solar cells (DSSCs) have been immensely focused on one of the most promising third-generation solar cells. The highest conversion efficiency of DSSC achieved after three decades of research is more than 14%, but the commercialization of this technology is still a challenge. In this review paper, an attempt has been made to present the comparison of different articles published, that gives the in-depth study of recent developments in various types of DSSCs based on architectural assembly and physical appearance. An overview of the limitations and challenges with their possible improvement strategies have also been discussed. This review paper concludes that appropriate selection of electrolytes dramatically affects the performance of DSSC, and quasi-solid-state electrolyte proves to be a better option. Besides, it also concludes that tandem structures are widely agreed with the approach to expand light utilization spectrum for an overall increase in its performance. However, still, the research is required, which could efficiently widen the applications of the DSSCs.